Blood Trihalomethanes and Human Cancer: A Systematic Review and Meta-Analysis - Miaomiao Fu; Pengyu Xue; Zhuorong Du; Jingsi Chen; Xiaojun Liang; Jiafu Li (Toxics)
The control of waterborne diseases through water disinfection is a significant advancement in public health. However, the disinfection process generates disinfection by-products (DBPs), including trihalomethanes (THMs), which are considered to influence the occurrence of cancer. This analysis aims to quantitatively evaluate the relationship between blood concentrations of THMs and cancer. Additionally, the relationship between blood chloroform concentration and cancer is analyzed separately. Following PRISMA guidelines, we conducted a thorough search in the PubMed, Web of Science, and CNKI databases. Statistical analysis was performed using Review Manager 5.4 software. After screening, seven studies meeting the evaluation criteria were included. A total of 1027 blood samples from patients with cancer and 7351 blood samples from the control group were collected. The average concentration of THMs in the blood of the experimental group was 46.71 pg/mL, while it was 36.406 pg/mL in the control group. The difference between the two groups was statistically significant (SMD = −0.36, 95% CI: −0.45 to −0.27, p < 0.00001). However, due to the limited research data on the relationship between blood THMs and cancer, the conclusions drawn exhibit high heterogeneity. Additionally, we discussed the carcinogenic mechanisms of THMs, which involve multiple biological pathways such as oxidative stress, DNA adduct formation, and endocrine disruption, with variations in accumulation and target sites potentially leading to different cancer types, for which evidence is currently lacking. In the future, further epidemiological and animal model studies on THMs should be conducted to obtain more accurate conclusions.